EDUCATIONAL COMPETENCE IN DIDACTICS AND METHODS OF PERSON-ORIENTED TRAINING - Khutorskiy, A.V. (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the notion of educational competence, its functions, and structural components.